The world of bullying: antecedents, consequences, and future pathways of workplace bullying - Annisa Savira Alifia; Fiona Niska Dinda Nadia; Nuri Herachwati; Ansar Abbas (BISMA (Bisnis dan Manajemen), 2024)
Workplace bullying is a widespread problem that has received great attention in academic studies in various fields. This research aims to facilitate future research by identifying the antecedents and consequences of workplace bullying. To answer the research question, a systematic literature review (SLR) methodology was used. The Scopus-indexed database journal was used to gather previous articles regarding workplace bullying, with 40 journals reviewed. This research found that workplace bullying occurs widely across industries and countries and negatively impacts the individuals affected by the bullying (victims) and the organisation. In addition, a model has been developed to examine the antecedents and consequences of workplace bullying to understand its impact more comprehensively. Through a comprehensive analysis of existing literature, this research uncovered trends and patterns in workplace bullying that had not previously been identified. The findings revealed an intriguing discrepancy between the predominant focus of previous studies on workplace bullying on the individual level and under-researched on the organisational level. Moreover, the Asian context has been overlooked in this field of inquiry. Therefore, there is a compelling rationale for conducting multilevel research in the context of Asia and developing countries to enhance our comprehension of this complex phenomenon.